Conditional survival in pediatric malignancies: Analysis of data from the Childhood Cancer Survivor Study and the Surveillance, Epidemiology, and End Results Program. Issue 7 (29th December 2014) - Mertens, Ann C.; Yong, Jian; Dietz, Andrew C.; Kreiter, Erin; Yasui, Yutaka; Bleyer, Archie; Armstrong, Gregory T.; Robison, Leslie L.; Wasilewski‐Masker, Karen
<x xml:space="preserve">Abstract</x> BACKGROUND Long‐term survivors of pediatric cancer are at risk of life‐threatening late effects of their cancer. Previous studies have shown excesses in long‐term mortality within high‐risk groups defined by demographic and treatment characteristics. METHODS To investigate conditional survival in a pediatric cancer population, the authors performed an analysis of conditional survival in the original Childhood Cancer Survivor Study (CCSS) cohort and the Surveillance, Epidemiology, and End Results (SEER) database registry. The overall probability of death for patients at 5 years and 10 years after they survived 5, 10, 15, and 20 years since cancer diagnosis and cause‐specific death in 10 years for 5‐year survivors were estimated using the cumulative incidence method. RESULTS Among patients in the CCSS and SEER cohorts who were alive 5 years after their cancer diagnosis, within each diagnosis group at least 92% were alive in the subsequent 5 years, except for patients with leukemia, of whom only 88% of 5‐year survivors remained alive in the subsequent 5 years. The probability of all‐cause mortality in the next 10 years among patients who survived at least 5 years after diagnosis was 8.8% in CCSS and 10.6% in SEER, approximately 75% of which was due to neoplasms as the cause of death. CONCLUSIONS The risk of death among survivors of pediatric cancer in 10 years can vary between diagnosis groups by at most 12%, even up to 20 years after diagnosis. This information is clinically significant when counseling patients regarding their conditional survival, particularly when survivors are seen in long‐term follow‐up. Cancer 2015;121:1108–1117. © 2014 American Cancer Society.